PENGARUH IKLIM KOMUNIKASI ORGANISASI DAN KOMUNIKASI ANTARPRIBADI TERHADAP KINERJA PEGAWAI YAYASAN AR-RISALAH AL-KHAIRIYAH TANJUNG MORAWA KABUPATEN DELI SERDANG - Suhendri Hendri (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2017)
Abstract: The purpose of this research is to provide an analytical explanation for; first, The Effect OfOrganizational Communication Climate on Employee Performance . Second, The Effect Of InterpersonalCommunication On Employee Performance. Third, The Effect Of Organizational Communication ClimateAnd Interpersonal Communication On Performance Of Employees At Ar-Risalah Al-Khairiyah FoundationTanjung Morawa District Deli Serdang. With questionaires that had been distributed to 37 employees,the main data to be analyzed were gathered. Data analysis using a quantitative approach with linearregression analysis. Also the data process and its analysis were performed with software SPSS to calculateeffect coefficient and furthermore, to be interpreted.